Seguridad Alimentaria en los hogares de Acandí. La disponibilidad de los alimentos como indicador de suficiencia alimentaria (2004)
ABSTRAC: The aim of this paper was to analize the variety and sufficiency of food from food availability per week data in a sample of rural and urban households from Acandí (Chocó, Colombia). Model of research: A descriptive research to obtain indicators of prevalence. Methods: A representative sample of 326 households (95% confidence interval and 5% error) was drawn from the local census of the townhall to analize the difference of mean available food items by settlements within the area. Moreover it was observed the frecquency of households with available food items by group of foods, the number of different items by group and, finally, the mean per capita/day adequacy of the obtained availability. Results: Variety of food items determined by mean food availability per week was 23±7 and 29±7 (p<0,001) in rural and urban households, respectivelly. A high proportion of rural and urban households had availability across all food groups although with a rather low variety of items. Availability in terms of food amount in g/capita/day did not showed statistically significant differences between rural and urban areas, except for dairy group (p<0,001), vegetables (p=0,012), tubers and bananas (p<0,001) and fat (p<0,001). The adequacy of the availability was low except for the sugar and fat groups. Conclusions: In spite households from Acandí had availability for all food groups that was not a condition to meet food sufficiency due to the low variety of items by group and the low availability in g/per cápita/day.